Proton pump inhibitors use and risk of inflammatory bowel diseases: a meta-analysis of observational studies - Shastri, Sanjana Aditya; Kantamneni, Raveena; Rashid, Muhammed; Chandran, Viji Pulikkel; Suhita, Ramadugula; Begum, Izwath; Nair, Sreedharan; Thunga, Girish (Medicine and Pharmacy Reports, 2022)
Background and objective. Proton Pump Inhibitors (PPIs) reduce gastric acid production and they are indicated for myriad gastrointestinal conditions. Prolonged use of PPI has been linked to the risk of inflammatory bowel disease (IBD) though this fact is not well established. We aimed to conduct a systematic review and meta-analysis to estimate the risk of IBD occurrence with PPI use. Methodology. The databases such as PubMed, Scopus, and Cochrane Library were accessed from inception to December 2020. Additionally, the bibliographic search and a random search in Google, Google Scholar, and ResearchGate were performed to find additional sources. The observational studies estimating the risk of IBD following the use of PPI, published in the English language were considered for this review. The methodological quality of included studies was assessed using the Modified Downs and Black checklist. Results. Eight out of 2038 studies with 157,758 participants were included in this meta-analysis. A significantly higher risk of IBD (adjusted odds ratio [aOR] 2.43; 95% Confidence Interval [CI] 1.18-5.02; P=0.02; n=6) was observed in participants taking PPIs for any indication. Moreover, a significant association was observed between PPI exposure on the different types of IBD such as ulcerative colitis and Crohn’s disease together (aOR: 3.60; 95% CI: 1.10-11.74), collagenous colitis (OR: 4.73; 95% CI: 1.99-11.22) and lymphocytic Colitis (OR: 3.77; 95% CI: 2.91- 4.87), but not with ulcerative colitis (P=0.47) and microscopic colitis (P=0.07) alone. Similarly, a significant association was observed among Europeans (aOR: 3.98; 95% CI: 2.36-6.71), but not with North American (aOR: 0.48; 95% CI: 0.01- 26.71) studies. Overall the study quality was good. Conclusion. The current evidence indicates that exposure to PPI is significantly associated with increased risk of IBD. Further, adequately powered studies from various parts of the world are needed for better quantification and generalizability of our findings. PROSPERO Protocol Registration Number: CRD42020209674